Algunas precisiones sobre las encuestas electorales (2010)
ABSTRACT: The presidential election of Colombia of 2010 for the period 2010-2014 took place the 30 of May of 2010 and its process of scrutiny officially finished the 8 of June of 2010. Nevertheless, the results of this scrutiny showed that mathematically, no candidate reached the absolute majority of the votes reason why one second return was carried out day 20 of June, which gave like winner to the candidate Juan Manuel Santos, (69,13%) who was chosen president by the higher number of voters and without precedents in the history of the Colombian democracy. Mockus only obtained the 27,47% of the preferences.